Askese inden for hinduisme: Et forsøg på typologisering - Marianne Qvortrup Fibiger (Religionsvidenskabeligt Tidsskrift, 2016)
The aim of this article is to put forward a proposal for an extended typology of asceticism within Hinduism, which not only includes the religious virtuosos in the form of a durative ascetism but also the dynamic and iterative asceticism as it is expressed in the āśrama system (stages of life). Thus it is argued that asceticism is a common point of refererence for most forms of Hinduism and thus the glue that binds the tradition together.